'A giant mess' – making sense of complexity in the accounts of people with fibromyalgia. (24th January 2013) - Dennis, Nicola L.; Larkin, Michael; Derbyshire, Stuart W. G.
<x xml:space="preserve">Abstract</x> Objectives The diagnosis of fibromyalgia is based on self‐report and indirect measures and thus is unavoidably influenced by patients' own understanding of their symptoms. In order to provide appropriate support for people with fibromyalgia, it is important to understand variation in patients' interpretations of their own symptoms. Methods Twenty people with fibromyalgia participated in email interviews exploring their experiences, history and diagnosis. Respondents answered a series of questions in their own time. Rich accounts were elicited. A hermeneutic phenomenological approach linked two stages of analysis. In the first instance, an in‐depth, inductive analysis was developed around a subset of eight transcripts, using interpretative phenomenological analysis. The outcomes of this work were then used to inform a template analysis, which was applied to the remaining 12 transcripts, in order to extend and check the credibility of the in‐depth analysis. Results Participants described enduring the course of a 'giant mess' of unpleasant symptoms, some of which were understood to be symptoms of fibromyalgia and some the interactive or parallel effects of comorbid illness. The respondents also demonstrated their considerable efforts at imposing order and sense on complexity and multiplicity, in terms of the instability of their symptoms. They expressed ambivalence towards diagnosis, doctors and medication, and we noted that each of the above areas appeared to come together to create a context of relational uncertainty, which undermined the security of connections to family, friends, colleagues and the workplace. Conclusions Three key issues were discussed. First, there was not one overall symptom (e.g., pain) driving the unpleasantness of fibromyalgia; second, participants spent excessive time and energy trying to manage forces outside their control; third, because there is no definitive 'fibromyalgia experience', each diagnosis is unique, and our participants often appeared to be struggling to understand the course of their illness. Issues of stigma and legitimacy need to be considered carefully by health professionals in the context of the complex and uncertain experience of patients. Statement of contribution What is already known on this subject? Diagnosis of fibromyalgia is based on exclusion of clinical problems combined with symptom report. Diagnosis is therefore uncertain, controversial and personal. Previous studies have suggested that the experience of fibromyalgia is defined by pain, fatigue and cognitive difficulties. What does this study add? There is not one overall symptom, including pain, which drives the unpleasantness of the experience of fibromyalgia. Salient difficulties may be diffuse and changeable. Fibromyalgia is experienced as intrusively embodied and worryingly variable. In the absence of established treatment pathways subjective patient interpretations of their symptom patterns become increasingly personal and complex. This study adopts reasonably novel methodological features, firstly to engage with participants who might find face‐to‐face interviews tiring and inconvenient, and secondly to combine in‐depth, bottom‐up qualitative analyses with more top‐down processes, in order to increase credibility, coherence and transferability.